78. Image quality metrics analysis to assess the reliability of injected activity reduction for 18F-FDG PET/MRI pediatric oncology examinations. (December 2018) - De Monte, F.; Zorz, A.; Branchini, M.; Zucchetta, P.; Bodanza, V.; Bui, F.; Paiusco, M.
Abstract : Purpose: the aim of this study was to evaluate the stability of image quality (IQ) metrics in pediatric 18F-FDG PET/MR acquisitions while decreasing statistical counts, mimicking an injected activity reduction. Methods: 21 18F-FDG PET/MR whole body acquisitions performed on an hybrid scanner (Biograph mMR, Siemens Healthcare) were retrospectively reconstructed with the e7-tools package. The full tracer activity (FTA) list-mode data (3 MBq/kg, 5 min/bed position) were truncated at 4, 3, 2.5, 2 and 1 min, simulating lower tracer activity (LTA) images corresponding to 2.4, 1.8, 1.5, 1.2 and 0.6 MBq/kg. Subjective IQ (score 1 to 5) and number of detectable lesions were assessed by two expert nuclear medicine physicians. SUV metrics (SUVmean, SUVmax and SUVpeak) and semi-quantitative parameters as contrast-to-noise ratio (CNR), normalized noise in liver (NN), metabolic tumor volume (MTV) and total lesion glycolysis (TLG) were evaluated on each image. Results: Results of subjective IQ evaluations are reported in Fig. 1; the assigned score decreased when reducing tracer activity, but remained acceptable till 1.5 MBq/kg. All the total 56 lesions were detected until 1.2 MBq/kg activity level, whereas 5 lesions were missed on the 0.6 MBq/kg image. Results of quantitative analysis are collected inTable 1, espressed as a ratio of LTA and FTA values. Semi-quantitative parameters (except SUVpeak) and IQ metrics showed limited variation respect to the FTA image until 1.5 MBq/kg image. Differences were not statistically significant in LTA images down to 1.5 MBq/kg with pairwise paired Wilcoxon and t-tests. SUVpeak is the parameter less affected by dose reduction (average difference for all LTA images inferior than 2%). NN showed a constant increase while decreasing statistical counts. Conclusions: An injected activity reduction up to 50% (1.5 MBq/kg) guarantees a stability in semi-quantitative parameters representing lesion detectability and tumor burden information.